Sintered artificial sand

JP2026174767APending Publication Date: 2026-10-30JFE MINERAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2026191947
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2026-08-21
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

【0010】 性能が改善された焼結人工砂を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026174767000001_ABST
    Figure 2026174767000001_ABST
Patent Text Reader

Abstract

To provide sintered artificial sand with improved performance. [Solution] A sintered artificial sand 1 containing multiple fibrous crystals 2 having a fiber diameter D3 of 0.5 μm or more and 30 μm or less, and a fiber length L of 0.5 μm or more and 50 μm or less, wherein the fibrous crystals 2 are mullite crystals or corundum crystals and their surfaces are covered with quartz, and among the fibrous crystals 2, fibrous crystals 2a obtained by dividing the fiber length L by the fiber diameter D3 are defined as the first fibrous crystals, and the area ratio X of the first fibrous crystals in relation to the area of ​​the sintered artificial sand 1 is 40% or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to sintered artificial sand.

Background Art

[0002] There are a technique for forming artificial sand, and a technique for solidifying artificial sand with a curing agent to form a mold. Patent Document 1 describes the pore diameter and pore volume determined by a mercury intrusion porosimeter as the uneven shape characteristics of refractory sintered particles. In addition, Patent Document 2 describes crystals having gaps formed by overlapping crystals among the crystals of sintered artificial sand.

Prior Art Literature

Patent Documents

[0003]

Patent Document 1

Patent Document 2

Summary of Invention

Problems to be Solved by the Invention

[0004] The performances of the refractory sintered particles described in Patent Document 1 and the sintered artificial sand described in Patent Document 2 were not sufficient.

[0005] An object of the present invention is to provide sintered artificial sand with improved performance.

Means for Solving the Problems

[0006] To achieve the above objective, a sintered artificial sand according to one aspect of the present disclosure is a sintered artificial sand containing a plurality of fibrous crystals having a fiber diameter of 0.5 μm or more and 30 μm or less and a fiber length of 0.5 μm or more and 50 μm or less, wherein the fibrous crystals are mullite crystals or corundum crystals and their surfaces are covered with quartz, and among the fibrous crystals, those with an aspect ratio of 2 or more obtained by dividing the fiber length by the fiber diameter are defined as first fibrous crystals, and the area ratio of the first fibrous crystals to the area of ​​the sintered artificial sand is 40% or more. Sintered artificial sand. The gist of this is...

[0007] Furthermore, the diameter of the sintered artificial sand may be between 30 μm and 1000 μm.

[0008] Furthermore, analysis using Raman spectroscopy at multiple locations in the sintered artificial sand revealed that quartz may be present at more than 80% of the aforementioned locations.

[0009] Furthermore, subcombinations of the aforementioned feature groups can also constitute an invention. [Effects of the Invention]

[0010] We can provide sintered artificial sand with improved performance. [Brief explanation of the drawing]

[0011] [Figure 1] This is an SEM image of sintered artificial sand according to the first embodiment. [Figure 2] This is a schematic diagram showing how two sintered artificial sands according to the first embodiment are in contact with each other. [Figure 3] Figure 2 is a schematic diagram showing the external shape of sintered artificial sand when viewed in a longitudinal cross-section. [Figure 4] This is a schematic diagram of the fibrous crystal according to the first embodiment. [Figure 5] This is a schematic diagram of an SEM image taken of sintered artificial sand according to the first embodiment. [Figure 6]This is a diagram showing the results of performing a fluidity test method on the sintered artificial sand according to the first embodiment of the present technology and the sintered artificial sand according to Comparative Example 1. [Figure 7] This is an SEM image of the sintered artificial sand according to Comparative Example 1. [Figure 8] This is a schematic diagram showing the sintered artificial sand according to Comparative Example 1. [Figure 9] This is a diagram showing the results of measuring the amount of change in electrical conductivity of the sintered artificial sand according to the first embodiment of the present technology and the sintered artificial sand according to Comparative Example 2. [Figure 10] This is a diagram showing the results of measuring the uniaxial compressive strength of the test piece according to the first embodiment of the present technology and the test piece according to Comparative Example 2. [Figure 11] This is a flowchart illustrating the method for producing sintered artificial sand according to the first embodiment of the present technology. [Mode for Carrying Out the Invention]

[0012] Hereinafter, an example of the sintered artificial sand according to the embodiment of the present technology will be described with reference to the drawings. The mold may be, for example, a casting mold, and the mold itself may be left unprocessed, or processed into a product for building materials and the like. The present technology is not limited to the following examples. In addition, the effects described in the present specification are illustrative and not limiting, and other effects may be provided.

[0013] [First Embodiment] ≪Overview≫ In general, when forming a mold using sintered artificial sand, a binder and an activator that cures the binder are used to bond the sintered artificial sand particles to each other. As the binder, a furan resin that cures by reacting with an acid is known. As the activator for curing the furan resin, for example, an activator containing an acid such as alkylbenzenesulfonic acid or sulfuric acid is used. Sintered artificial sand is a refractory particle, and the formed mold is used, for example, as a casting mold.

[0014] Sintered artificial sand is generally manufactured by sintering granulated raw material powder at high temperatures using a rotary kiln. Sintered artificial sand may contain impurity metal minerals. Impurity metal minerals include, for example, substances derived from the raw materials, substances mixed in or attached during the manufacturing process, and additives. Examples of impurity metal minerals include Fe2O3, TiO2, Cr2O3, and SiO2. Such impurity metal minerals are acid-reactive substances that readily react with acids.

[0015] Incidentally, if the sintered artificial sand contains too much of the aforementioned acid-reactive substances, the acid in the activator added to react with the furan resin may be largely consumed by the impurity metal minerals contained in the sintered artificial sand. When a large amount of the activator acid is consumed by the impurity metal minerals, the amount of acid that reacts with the binder will be relatively reduced, which may affect the hardening reaction of the binder. If the hardening reaction of the binder is suppressed, it may affect the strength of the sand mold produced.

[0016] Furthermore, in sand mold production using 3D additive manufacturing, the surface of the sand mold immediately after production has numerous individual sintered artificial sand particles attached, with activators adhering to them but not bound to other sintered artificial sand particles. These individual sintered artificial sand particles are removed from the sand mold using, for example, a brush or air blower. It is desirable that these individual sintered artificial sand particles be easily removed from the sand mold. The activators added to react with the furan resin create surface tension between the sintered artificial sand particles that are in contact with each other. As a result, the activators increase the cohesiveness of the sintered artificial sand particles in contact with each other and reduce their fluidity. The higher the fluidity of the sintered artificial sand, the easier it is to remove it from the sand mold. This is because high fluidity means that the sintered artificial sand is less sticky.

[0017] <<Composition of Sintered Artificial Sand>> The structure of the sintered artificial sand according to the first embodiment of this technology will be described below with reference to Figures 1 to 5. Figure 1 is an SEM image of the sintered artificial sand 1. Figure 2 is a schematic diagram showing how two sintered artificial sands 1 are in contact with each other. Figure 3 is a schematic diagram showing the external shape of the sintered artificial sand 1 when viewed in a longitudinal cross-section. The sintered artificial sand 1 is composed of a large number of fibrous crystals 2. More specifically, the sintered artificial sand 1 is a fibrous granule composed mainly of aggregated fibrous crystals 2. Fibrous crystals 2 are columnar crystals (whiskers).

[0018] Sintered artificial sand 1 contains at least one of mullite crystals and corundum crystals as fibrous crystals 2. Mullite crystals are crystals of aluminosilicate. Corundum crystals are crystals of aluminum oxide. It is known that the shape of mullite crystals can be controlled, for example, by changing the chemical composition. Therefore, columnar mullite crystals can be obtained by adjusting the chemical composition, etc. The same applies to corundum crystals. The surface of fibrous crystals 2 is covered with quartz.

[0019] The sintered artificial sand 1 may be spherical or deformed. As shown in Figure 2, the maximum particle diameter D1 of the sintered artificial sand 1 is, for example, the distance between the two points furthest apart on the outer surface of the sintered artificial sand 1. If the sintered artificial sand 1 is spherical, the maximum particle diameter D1 is the diameter of the sintered artificial sand 1. The maximum particle diameter D1 is, for example, about 30 μm or more and 1000 μm or less. More preferably, the maximum particle diameter D1 is, for example, about 30 μm or more and 200 μm or less.

[0020] Numerous fibrous crystals 2 can be observed on the surface of the sintered artificial sand 1 shown in Figure 1. The fibrous crystals 2 exposed on the surface of the sintered artificial sand 1 form irregularities on the surface of the sintered artificial sand 1, as shown in Figure 3. When the surface of the sintered artificial sand 1 is irregular, the activators 3 will be located in a point-like manner between the sintered artificial sand 1 that are in contact with each other due to surface tension, either when the sand mold comes into contact with the sintered artificial sand 1 in a single state, or when the sintered artificial sand 1 come into contact with each other in a single state. When the contact portion 3A of the activators 3 is located in a point-like manner between the sintered artificial sand 1, the area over which surface tension acts is reduced, thereby suppressing the cohesiveness of the sintered artificial sand 1 and making it easier for the sintered artificial sand 1 to separate from each other. In this embodiment, the cohesiveness of the sintered artificial sand 1 is suppressed by forming irregularities on the surface of the sintered artificial sand 1.

[0021] Since the surface irregularities of the sintered artificial sand 1 were considered to be an important factor influencing the cohesiveness of the sintered artificial sand after the activator was attached, the proportion of fibrous crystals 2 exposed on the surface of the sintered artificial sand 1 was quantified as a means of evaluating the degree of irregularities. Therefore, an SEM image of the sintered artificial sand 1 was taken using a scanning electron microscope (SEM), and the dimensions of the fibrous crystals 2 captured in the SEM image were measured to evaluate the exposed fibrous crystals 2. First, as preparation for taking the SEM image, the sintered artificial sand 1 according to this embodiment was applied to a carbon tape, and osmium was deposited as a conductive treatment. Then, using a Carl Zeiss Sigma500 SEM, an SEM image of the sintered artificial sand 1 was obtained at an acceleration voltage of 1kV and a magnification of 500x. Subsequently, the fiber diameter D3 and fiber length L of each fibrous crystal 2 were measured using an image analysis device (WinROOF, manufactured by Mitani Corporation) based on the obtained SEM image (Figure 4).

[0022] Image P shown in Figure 5 is a schematic diagram of the captured SEM image. The measurement of fibrous crystals 2 will be explained with reference to Image P. Although Image P shows the entire sintered artificial sand 1, only the fibrous crystals 2 located in region P1, a part of the sand, were evaluated and their dimensions were measured. Region P1 is a circular region located in the center of the sintered artificial sand 1 in Image P. Note that in Figure 5, the fibrous crystals 2 located outside region P1 are not shown. The diameter D2 of region P1 was set to 1 / 2 of the maximum particle diameter D1 of the sintered artificial sand 1.

[0023] The overlap between the fibrous crystals 2 exposed on the surface of the sintered artificial sand 1 is minimal. Therefore, the fiber diameter D3 and fiber length L of the fibrous crystals 2 could be measured accurately. Alternatively, the width of the fibrous crystals 2 as seen in the SEM image may be measured as the fiber diameter D3. The fiber diameter D3 of the fibrous crystals 2 shown in Figure 4 is measured based on the algorithm executed by the CPU of the image analysis device described above. The fiber diameter D3 may be, for example, the arithmetic mean of fiber diameters D3 measured at multiple locations along the fiber length L direction. The fiber length L is measured based on the algorithm executed by the CPU of the image analysis device described above. The fiber length L may be, for example, the arithmetic mean of fiber lengths L measured at multiple locations along the fiber diameter D3 direction. Note that Figure 4 is a schematic diagram of the fibrous crystals 2, and the shape of the fibrous crystals 2 is not limited to that shown in Figure 4.

[0024] For example, sintered artificial sand 1 may contain multiple fibrous crystals 2 having a fiber diameter D3 of approximately 0.5 μm to 30 μm and a fiber length L of approximately 0.5 μm to 50 μm. Alternatively, sintered artificial sand 1 may contain multiple fibrous crystals 2 having a fiber diameter D3 of approximately 0.5 μm to 10 μm and a fiber length L of approximately 0.6 μm to 50 μm. More preferably, sintered artificial sand 1 may contain multiple fibrous crystals 2 having a fiber diameter D3 of approximately 1 μm to 7 μm and a fiber length L of approximately 1 μm to 40 μm. The aspect ratio (fiber length L / fiber diameter D3) of each fibrous crystal 2 was calculated from the measured fiber diameter D3 and fiber length L. Then, from the multiple fibrous crystals 2 whose dimensions were measured, fibrous crystals 2 with an aspect ratio of 2 or more were extracted. Fibrous crystals 2 with an aspect ratio of 2 or greater are called fibrous crystals 2a, distinguishing them from fibrous crystals 2 with an aspect ratio less than 2. When fibrous crystals 2a are not distinguished from fibrous crystals 2 with an aspect ratio less than 2, they are simply called fibrous crystals 2. The fiber diameter D3 and fiber length L of fibrous crystals 2a are within the ranges of the aforementioned fiber diameter D3 and fiber length L values. Fibrous crystals 2a correspond to the first fibrous crystal.

[0025] Next, the area S1 of the fibrous crystal 2a was calculated. The area S1 is calculated based on the algorithm executed by the CPU of the image analysis device described above. The area S1 may be calculated based on, for example, the fiber diameter D3 and the fiber length L. Alternatively, for example, the number of pixels forming the fibrous crystal 2a on the SEM image may be directly extracted by various image processing methods and used as the area S1.

[0026] Next, we determine the total area S2 (S2 = ΣS1) of the multiple fibrous crystals 2a within region P1. We also determine the area of ​​region P1. The area S3 of region P1 is calculated from the diameter D2 of region P1 (S3 = π × (D2 / 2)). 2 ). From the total area S2 of the obtained fibrous crystal 2a and the area S3 of region P1, the area fraction X(%) of the total area S2 occupying region P1 is calculated according to Equation 1. Area ratio X(%)=(S2 / S3)×100 (1)

[0027] The area ratio X is preferably around 40% or more. To suppress cohesion, it is desirable for the area ratio X to be as high as possible. If the area ratio X is too small, the surface irregularities of the sintered artificial sand 1 will not be sufficient, increasing the contact area between the sintered artificial sand 1 particles and causing a decrease in cohesion performance. Considering that there are also fibrous crystals 2 with an aspect ratio smaller than 2, the maximum value of the area ratio X will be less than 100%. The area ratio X may be, for example, between 40% and 60%.

[0028] The following describes the results of a fluidity test performed on sintered artificial sand 1 according to the first embodiment of this technology and sintered artificial sand 1A according to Comparative Example 1, with reference to Figure 6. The fluidity test method is the method described on page 57 of "Test Methods for Molds and Mold Materials" (published by the Small and Medium Enterprise Agency, Tokyo: Information and Technology Department, Small and Medium Enterprise Agency, May 1999). Briefly, in the fluidity test, the sand is sieved, and the fluidity is evaluated by the percentage of sand remaining on the sieve screen. A lower percentage of sand remaining on the screen indicates higher fluidity (lower cohesiveness). The above test method uses resin (binder in this paper) and hardener (activator in this paper), but this time only the activator will be evaluated. The reason for evaluating only the activator is that when adding liquid binder and activator to sand, the activator is added first and mixed with the sand once. If the sand is sticky at that stage, it will adhere to the walls of the mixing container, etc., worsening the workability of subsequent processes. Furthermore, in sand mold 3D additive manufacturing, which has seen significant development in recent years, the aforementioned stickiness also poses a problem in the process of removing sand that has adhered only to the activator from a sand mold solidified by the activator and binder. The degree of influence of this stickiness is evaluated by the fluidity (cohesiveness) of the same test method. As shown in Figure 6, the residue rate on the mesh of sintered artificial sand 1A of Comparative Example 1 was 7.6%, while the residue rate on the mesh of sintered artificial sand 1 of this technology was 0.5%, indicating that the cohesiveness has been improved in this technology. The differences between sintered artificial sand 1 of this technology and sintered artificial sand 1A of Comparative Example 1 are explained below.

[0029] The surface of sintered artificial sand 1A shown in Figure 7 is smoother and has fewer irregularities than the surface of sintered artificial sand 1 shown in Figure 1. Furthermore, almost no fibrous crystals are observed on the surface of sintered artificial sand 1A shown in Figure 7. Thus, the surface condition of sintered artificial sand 1A is significantly different from the surface condition of sintered artificial sand 1 in this technology. Therefore, as shown in Figure 8, when sintered artificial sand 1A comes into contact with each other, the activator 3 spreads and comes into contact with the sintered artificial sand 1A over a wider area than in this technology shown in Figure 3. As a result, the sintered artificial sand 1A is less likely to separate due to surface tension, and it is thought that the cohesiveness of the sintered artificial sand 1A is increased.

[0030] Next, the quartz covering the surface of the fibrous crystal 2 will be described in more detail. In this embodiment, coating the surface of the fibrous crystal 2 with quartz suppresses the consumption of the activator acid by the impurity metal minerals contained in the sintered artificial sand 1. The quartz referred to here is crystalline silicon dioxide, which has different physical properties from amorphous silicon dioxide. In this embodiment, crystalline silicon dioxide is called quartz, and amorphous silicon dioxide is called amorphous silica to distinguish between them. Amorphous silica is an unstable substance that reacts with acid. In contrast, quartz has the property of being less reactive with acid. It is desirable that as wide an area as possible on the surface of the fibrous crystal 2 is covered with quartz, but there may be parts of the surface of the fibrous crystal 2 that are not covered with quartz. Furthermore, it is not excluded that fibrous crystals 2 that are not covered with quartz may be included in the sintered artificial sand 1.

[0031] The following describes the results of detecting quartz present in sintered artificial sand 1 using Raman spectroscopy. A JASCO NRS-5100 Raman spectrophotometer was used, with an excitation wavelength of 531.9 nm and a wavenumber resolution of 1 cm. -1Five measurements were taken for each sintered artificial sand sample using a 100x objective lens at a measurement depth of approximately 1 μm. The Raman spectroscopy measurements were used to examine the presence or absence of peaks originating from the quartz crystal structure. Where peaks originating from the quartz crystal structure were observed, it could be determined that quartz was present. For example, if the value obtained by dividing the peak intensity Ia originating from the quartz crystal structure by the peak intensity Ib originating from the mullite structure (hereafter referred to as the A value) is 1 or greater (1 ≤ A = Ia / Ib), it could be determined that quartz was present. Note that the quartz peak is located at 800 cm⁻¹ in the Raman spectrum. -1 It appears in the vicinity (symmetric vibration of SiO2), and the peak of the mullite crystal is at 940 cm⁻¹ in the Raman spectrum. -1 It appears in the vicinity.

[0032] Raman spectroscopy was performed at five points on a single grain of sintered artificial sand 1, and the result showed that the quartz content was 80% or higher. More specifically, the fibrous crystal 2 containing quartz was 80% or higher. Furthermore, it was found that a quartz content of 80% or higher suppresses the consumption of the activator acid by the impurity metal minerals contained in the sintered artificial sand 1.

[0033] The reactivity with acid was evaluated for both the sintered artificial sand 1 according to the first embodiment of this technology and the sintered artificial sand 1B according to Comparative Example 2, by measuring the change in conductivity. The quartz content in the sample of sintered artificial sand 1 according to this technology was 85%, while the quartz content in the sample of sintered artificial sand 1B from Comparative Example 2 was 30%. Furthermore, the area ratio X of fibrous crystals 2a in sintered artificial sand 1B was equivalent to the area ratio X of fibrous crystals 2a in sintered artificial sand 1.

[0034] Specifically, 50 ml of 0.1 M hydrochloric acid and 50 ml of deionized water were added to 50 g of sintered artificial sand, stirred with a stirrer for 20 minutes, and then filtered. The conductivity of the filtrate and the blank solution (the same procedure performed with only hydrochloric acid and deionized water, without sintered artificial sand) was measured, and the difference in conductivity between the filtrate and the blank solution was defined as the "change in conductivity." The conductivity of the deionized water and the blank solution in this test was 1.36 × 10⁻⁶, respectively. -3The values ​​were mS / cm and 19.5 mS / cm. The conductivity mentioned above is a commonly used measurement method to determine the total amount of ions contained in a solution. In this test, it was also used to comprehensively and simply index the amount of dissolved metal ions and the amount of change in ionized hydrochloric acid when impurities in the sintered artificial sand reacted with acid and dissolved. Figure 9 shows the results of the change in conductivity for sintered artificial sand 1 of this technology and sintered artificial sand 1B of Comparative Example 2. While the change in conductivity for sintered artificial sand 1B of Comparative Example 2 was 1.24 mS / cm, the change in conductivity for sintered artificial sand 1 of this technology was 0.10 mS / cm, indicating a decrease in the change in conductivity. Thus, by using sintered artificial sand 1 of this technology, it is possible to suppress the consumption of a large amount of activator acid by sintered artificial sand 1.

[0035] To verify the difference in strength between this technology and Comparative Example 2, sand mold test pieces using furan resin were prepared and their uniaxial compressive strength was measured. N-Fran GH-35K manufactured by Gun-ei Chemical Industry Co., Ltd. was used as the binder, and RPR-102A manufactured by Gun-ei Chemical Industry Co., Ltd. was used as the activator. The prepared test pieces were cylindrical with a diameter of 50 mm and a length of 5 cm. Figure 10 shows the results of the uniaxial compressive strength test for a test piece made with sintered artificial sand 1 according to the first embodiment of this technology and a test piece made with sintered artificial sand 1B according to Comparative Example 2. While the uniaxial compressive strength of the test piece from Comparative Example 2 was 0.0 kgf / 50φ, the uniaxial compressive strength of the test piece from this technology was 0.9 kgf / 50φ, indicating an improvement in strength. Thus, by using sintered artificial sand 1 from this technology, a significant decrease in the strength of the manufactured sand mold can be suppressed.

[0036] ≪Method for manufacturing sintered artificial sand≫ Referring to Figure 11, a method for producing sintered artificial sand according to the first embodiment of this technology will be described. First, in the crushing step S101, the raw materials are crushed to form a slurry to obtain a raw material liquid. The raw materials for sintered artificial sand are minerals such as bauxite. Bauxite is a mineral that contains a large amount of aluminum compounds such as aluminum oxide (Al2O3). In addition, bauxite contains impurities derived from the raw materials, such as iron (Fe), titanium (Ti), chromium (Cr), and silicon (Si). Then, in the granulation step S102, the slurryed raw material liquid is granulated to a size appropriate for the product by a known method such as spray drying to obtain raw material powder. Note that the obtained raw material powder may contain impurities derived from the process.

[0037] Next, in the sintering process of step S103, sintered artificial sand is obtained by heating (sintering) the granulated raw material powder. More specifically, in the sintering process, the raw material powder is heated using equipment such as a rotary kiln to obtain sintered artificial sand. The heating temperature of the raw material powder is, for example, around 1700°C to 1900°C. By heating the raw material powder at a high temperature, fibrous crystals 2 are grown in the raw material powder. More specifically, by heating the raw material powder at a high temperature, at least one of mullite crystals and corundum crystals is grown in the raw material powder.

[0038] Next, in the cooling step S104, the sintered artificial sand is cooled. The cooling step is a process of cooling the sintered artificial sand to a temperature of 400°C or lower, for example, by air cooling or water cooling. After that, in the grinding step S105, the surface of the sintered artificial sand is ground using a grinding machine to smooth out the unevenness of the surface of the sintered artificial sand. Then, in the classification step S106, the sintered artificial sand is sieved according to size. Classification methods include wind classification and vibrating screens.

[0039] Next, in the quartz formation step S107, a quartz film is formed on the surface of the fibrous crystal 2. For example, if there is an excess of SiO2 component present during mullite whisker synthesis, it may be used, but if there is not enough, additional SiO2 component may be added to form a quartz film on the surface of the mullite whisker particles. For example, after mullite whisker granulation, a quartz film may be formed using a wet coating method by the sol-gel method or a chemical film formation method by CVD (chemical vapor deposition). When forming a quartz film by the CVD method, for example, at atmospheric pressure or above, and in a medium vacuum (100 Pa to 10°C) -1 In a state of approximately Pa or less, a gaseous raw material can be introduced, and a quartz film can be formed on the surface of the fibrous crystals by heat, plasma, light, etc. Through the above process, sintered artificial sand 1 having fibrous crystals 2 can be obtained.

[0040] <<Main effects of the first embodiment>> In the sintered artificial sand according to the first embodiment of this technology, the area ratio of fibrous crystals 2a with an aspect ratio of 2 or more to the area of ​​the sintered artificial sand 1 is 40% or more. As a result, irregularities are formed on the surface of the sintered artificial sand, and the contact portions 3A of the activator 3 exist as points between the sintered artificial sand 1 that are in contact with each other. As a result, the cohesiveness of the sintered artificial sand 1 is suppressed, and the sintered artificial sand 1 can be easily separated from each other. This makes it possible to easily remove the sintered artificial sand that has adhered to the sand mold.

[0041] Furthermore, according to the sintered artificial sand of the first embodiment of this technology, since the surface of the fibrous crystals 2 is covered with quartz, it is possible to suppress the excessive consumption of the activator acid by the sintered artificial sand 1, and to prevent the amount of acid that reacts with the binder from becoming too small. This makes it possible to suppress a significant decrease in the strength of the sand mold.

[0042] Furthermore, according to the sintered artificial sand of the first embodiment of this technology, since quartz is present at more than 80% of the multiple positions of the sintered artificial sand 1, it is possible to suppress the excessive consumption of the activator acid by the sintered artificial sand 1 and to prevent the amount of acid that reacts with the binder from becoming too small. As a result, it is possible to suppress a significant decrease in the strength of the sand mold. [Other embodiments] As described above, a first embodiment of this disclosure has been presented, but the statements and drawings that constitute part of this disclosure should not be understood as limiting this disclosure. Various alternative embodiments, examples, and operating techniques will become apparent to those skilled in the art from this disclosure.

[0043] Furthermore, the configurations disclosed in the first embodiment can be combined as appropriate, within the bounds of consistency. Thus, this disclosure naturally includes various embodiments not described herein. Therefore, the technical scope of this disclosure is determined solely by the inventive features relating to the claims that are appropriate based on the above description. [Explanation of symbols]

[0044] 1…Sintered artificial sand 1A... Sintered artificial sand 1B... Sintered artificial sand 2,2a...Fibrous crystals 3…Activator 3A…Contact part D1…Maximum particle diameter D2…Diameter D3... Fiber diameter Ia, Ib… Peak intensity L... Fiber length P...Image P1…area S1…area S2...Total area S3…area X…Area ratio

Claims

1. This is a sintered artificial sand containing multiple fibrous crystals with a fiber diameter of 0.5 μm or more and 30 μm or less, and a fiber length of 0.5 μm or more and 50 μm or less. The fibrous crystal is a mullite crystal or a corundum crystal, and its surface is covered with quartz. Among the fibrous crystals, those fibrous crystals having an aspect ratio of 2 or more obtained by dividing the fiber length by the fiber diameter are defined as first fibrous crystals, and the area ratio of the first fibrous crystals to the area of ​​the sintered artificial sand is 40% or more. Sintered artificial sand.

2. The diameter of the sintered artificial sand is between 30 μm and 1000 μm. Sintered artificial sand according to claim 1.

3. Analysis of the sintered artificial sand using Raman spectroscopy revealed that quartz is present at more than 80% of the aforementioned locations. Sintered artificial sand according to claim 1 or 2.

Citation Information

Patent Citations

  • Sintered artificial sand

    JP2019084582A

  • Refractory aggregate for molding sand

    JP2024039204A